Compounding of Synthesized Monomethylol Urea and Hydroxylated Palm Kernel Oil as Composite Resin for Emulsion Paint Formulation - S, Archibong C.; Kime, Bintu; G, Fadawa F. (Darul Yasin Al Sys, 2024)
Palm kernel oil which is a triglyceride was subjected to chemical modification of its structure to add hydroxyl groups. The hydroxylated chemical structure was cross-linked with monomethylol urea, a thermoset resin to produce a composite MMU/HPKO. Fourier transform infrared spectroscopy was used to ascertain the existence of chemical interactions between MMU and HPKO, the reduction of the absorption band around 3360.69cm-1 which is due to the presence of hydroxyl groups was an indication of the occurrence of chemical reaction between hydroxylated palm kernel oil and monomethylol urea. The compounded composite was further characterized for the eval_uation of physical and mechanical properties. Properties like the elongation at break, viscosity, Gel time, Turbidity and Refractive index increases with percentage inclusion of HPKO until at above 50% where changes were noticed. While parameters like Formaldehyde emission, Moisture uptake, Density and melting point decreases with percentage loading of HPKO. Copolymerization successfully combined the advantages of MMU specie with HPKO while offsetting their shortcomings in a synergetic manner to create a higher performance class of polymer. Therefore, the blending of monomethylol urea with the hydroxylated palm kernel oil in this research work has added flexibility to MMU which hitherto was brittle and hard, improve it water resistance properties because of the hydrophobic nature of the hydroxylated palm kernel oil, and has brought about a reduction in the formaldehyde emission of monomethylol urea due to the percentage’s inclusion of hydroxylated palm kernel oil and subsequent deduction of monomethylol urea.